The Influence of Suppliers and Customers as a Micro External Environment on Sales Growth - Aulia Fitri, Diniyah (CV. Publikasi Indonesia, 2024)
A company is a for-profit organization, that is, an organization that has the goal of obtaining high profits. To achieve this goal, companies need to analyze the environment, both internal and external. The micro-external environment is usually referred to as the industrial environment. This is because, in this micro external environment, the company's business activities occur directly where there is a strong relationship between competitors, suppliers, and consumers themselves so that their impact and influence on each other can be seen. Indofood explained that rising geopolitical tensions, high inflation rates, and rising prices of various commodities created markets. This research uses a qualitative approach with a descriptive type. A qualitative approach is used to analyze the external environment using annual reports at PT. Indofood Sukses Makmur Tbk deals with data sourced from observations about external factors, written data in the form of documents, and information provided. This research will discuss the efforts made by Indofood to overcome this problem. Suppliers and customers are important factors in this. Both had a positive influence on sales growth of 11.56% with an operating profit margin of 17.8% despite an increase in sales prices to balance the increase in raw materials.